Learning, Teaching and Assessing Dance in Physical Education. (2nd September 2016) - El-Sherif, Jennifer L.
Abstract : Many physical educators have limited dance experience and may lack the skills, knowledge and confidence to teach dance in their school programs. Yet, including dance units in physical education curriculums can provide positive experiences for students who may not enjoy traditional instruction. This article provides step-by-step instructions for physical educators to learn and teach dance steps. Included are considerations for finding music, sample dance steps, dance sequences, and implementing PE Metrics to assess the performance of students in grades 3 through 12. Alignment to the student outcomes in dance, according to SHAPE America's National Standards and Grade-Level Outcomes for K-12 Physical Education, is also presented.